2018
DOI: 10.1080/17483107.2018.1498925
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations from the prosthetic and intact limb during standing on a sway-referenced support surface for transtibial prosthesis users

Abstract: Purpose: To investigate the bilateral postural adaptations as a result of standing on an increasingly unstable sway-referenced support surface with both the intact and prosthetic limb for transtibial prosthesis users (TPUs). Method: TPUs (n = 14) and matched controls (n = 14) stood quietly in multiple foot placement conditions (intact foot, prosthetic foot and both feet) on a sway-referenced support surface which matched surface rotation to the movement of the centre of pressure (CoP). Force and motion data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
2
8
1
1
Order By: Relevance
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%-38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n 5 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) [12][13][14][19][20][21][22][23]25,26,28,29,[31][32][33][34][35][36][37][38][39][40][41][42]44,45,47,48,[50][51][52][53][54][55][56]58,59,[62][63][64][65][66][67]…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%-38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n 5 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) [12][13][14][19][20][21][22][23]25,26,28,29,[31][32][33][34][35][36][37][38][39][40][41][42]44,45,47,48,[50][51][52][53][54][55][56]58,59,[62][63][64][65][66][67]…”
Section: Discussionsupporting
confidence: 69%
“…79,92,94,108-113 The equipment used across studies varied, but the most common was multiple force plates (Figure 2). 12,19-48,51-60,62-70,114-117 Motion capture systems were also common. 13,20,21,29,31-36,41,44,45,48,51,54,60,90,91,99,100,102,108,110,112,113,115-138 Single force platforms were also commonly used in studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a TTA, most individuals rely automatically on their intact leg during standing [3][4][5][6] and walking [7,8]. This strategy is even more pronounced in situations with increased demands for postural control [3,5,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Displacement of the center of mass in people with lower-limb amputation is higher in both the anterior-posterior and medial-lateral directions compared with controls without amputation. 17,19 It has also been noted that balance in people with lower-limb amputation is maintained through increased movements of the nonamputated limb and trunk, 18 likely because of the loss of proprioception and ankle control on the prosthetic limb. Thus, the energy required to stand may be greater in people with than without amputation because increased postural sway and increased center of mass displacement will require greater muscular activation and metabolic effort to maintain the standing position.…”
Section: Introductionmentioning
confidence: 99%